Desmopressin prescription safety in adult inpatients: a real-world tertiary centre experience - Muhammad Fahad Arshad; Sam Solanki; Luka Dancyger-Stevens; Madushani Karunanayaka; Ee-Wen Loh; Kyaw Naing Htoon; Mohanad Turki; Alia Munir (Endocrine Connections, 2025)
Omissions or delays in desmopressin can result in serious patient harm in patients with arginine vasopressin deficiency (AVP-D), formally known as cranial diabetes insipidus. Desmopressin administration practice in hospitals has not been thoroughly investigated previously. This study evaluated desmopressin prescription and administration practice at a large tertiary centre. A retrospective electronic case notes review of all admissions (≥24 h) with AVP-D between 2018 and 2021 at Sheffield Teaching Hospitals was undertaken. The outcomes were defined as the total number of missed and delayed doses, time to prescription and administration from admission and incidence of dysnatraemias. A qualitative survey to determine knowledge of AVP-D and desmopressin among staff members was also carried out. In total, 102 admissions were identified, of which 38% of admissions were via emergency department (ED). The total number of missed and delayed doses were 132/1315 (10.0%) and 139/1283 (10.9%), respectively. Of all admissions, 33% had ≥1 missed doses, while ≥1 doses were delayed in 54% admissions. ED rates of desmopressin prescription were low at 5%. The most common reasons documented for missed or delayed doses were unavailability of desmopressin followed by inability of the patient to take the medication. Median (interquartile range) prescription and administration times from admission were 5.6 (2.7–10.7) and 15.1 (8.7–27.0) h, respectively. The incidence of inpatient hypernatraemia and hyponatraemia was 7.6 and 30.4%, respectively. The staff survey showed below-average knowledge of the condition, advocating for an urgent need for education.